The Conseptual Model of Consumer Purchase Intentions to use Herbal Products - D. Widyaningtyas & W. Untoro (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Herbal Products has experienced significant growth in product demand. The usage of herbal products has increased.Herbal is often used as a complementary alternative medicine or as a main treatment. This study aims to propose aconceptual model to predict the consumer purchase intention to use herbal products, with modified theory of plannedbehavior (TPB). Key variables of TPB, Health Belief Model (HBM), and Protection Motivation Theory (PMT) are usedto develop this conceptual model. TPB provides a framework for studying attitudes toward behavior, with the mostimportant determinant being the intention to behave. HBM related to changes in health behaviors and psychologicalmodels with some key behavioral aspects with determinant perceived benefit and barrier. PMT is a development ofHBM that emphasizes the effective response and self-efficacy. This integration will provide a complete view ofconsumer behavior intention in using herbal products. A robust conceptual model formed. The implication of this study,it is hoped that an improved framework model can be obtained for predicting customer intention to purchase herbalproducts.Keywords: purchase intention, conceptual model, theory of planned behavior, health belief model, herbal products